Metachronous, non‐pineal, trilateral retinoblastoma in a patient with a seemingly reduced‐expressivity RB1 germline deletion. Issue 3 (18th March 2022) - Eiset, Saga Elise; Funding, Mikkel; Racher, Hilary; Heegaard, Steffen; Gallie, Brenda; Urbak, Steen Fiil; Gregersen, Pernille A.
Abstract: The clinical course of trilateral retinoblastoma can be unpredictable, and expressivity of germline RB1 variants may vary during development. We describe an unexpected fatal case of trilateral retinoblastoma with an intracranial tumor in an unusual location and discuss genetic copy number analyses as a useful diagnostic tool with therapeutic potential. Abstract : The clinical course of trilateral retinoblastoma can be unpredictable, and expressivity of germline RB1 variants may vary during development.